Characteristics and prognostic factors of TB loss to follow up (LTFU) in Malaysia – A 5-year retrospective cohort from 2014 to 2018 - Ahmad Yusri Abd Rani; Nurhuda Ismail; Yuslina Zakaria; Mohamad Rodi Isa (Journal of Infection and Public Health)
Background: Tuberculosis (TB) loss to follow-up (LTFU) disrupts treatment, compromises patient outcomes, and exacerbates public health challenges. This study evaluates the prevalence, time to LTFU, and prognostic factors of TB LTFU among adults in Malaysia between 2014 and 2018. Methods: A retrospective cohort analysis was conducted using national data from the MyTB database, comprising 97,542 TB patients. Kaplan-Meier analysis determined the time to LTFU, while Cox proportional hazards analysis identified significant prognostic factors. Results: The prevalence of TB LTFU decreased from 7.09 % in 2014 to 5.71 % in 2018. The mean time to LTFU was 54.8 days during intensive phase and 162.5 during continuation phase. Significant risk factors for LTFU included age < 65 years, male gender, urban residence, smoking, diabetes, and initiation of treatment at government facilities. Notably, the absence of Directly Observed Therapy (DOT) during the continuation phase markedly increased LTFU risk (adjusted HR 33.18; 95 % CI: 31.02–35.48). Conclusion: Despite a declining trend in TB LTFU prevalence, younger age, urban residence, and lack of DOT during continuation remain key challenges. Strengthening DOT implementation and targeted interventions for at-risk groups are crucial for reducing TB LTFU and improving treatment adherence.